(untitled) (Carte Romanze, 2021)
This article presents new findings in relation to the four vernacular text – by Cavalcanti, Dante, Cino, and allegedly Arnaut Daniel – cited in Petrarch’s ‘Lasso me, ch’i’ non so in qual parte pieghi’ (Rerum vulgarium fragmenta 70). It considers the knowledge and availability of these texts in Venice prior to the printing of three of them by Aldo Manuzio at the close of his 1514 reprint of Petrarch’s vernacular works. As part of this enquiry, special attention is given to the analysis of Antonio da Canal’s commentary to the Rerum vulgarium fragmenta, the dating of which is also reconsidered. The article also provides an edition of the section of this commentary dedicated to “Lasso me, ch’i’ non so in qual parte pieghi”.